Tendencii razvitija vidov sporta v Rossijskoj Federacii (po svedenijam Federal'nogo statisticeskogo nabljudenija No 5-FK) - Savenkova, E. A.; Mochalova, M. S. (Vestnik sportivnoj nauki; Sports science bulletin, 2021)
Issues related to the sphere of physical education and sports are national development goals of the Russian Federation (RF). The Decree of the President of the Russian Federation defines such priority goals in the development of the country as: creation of conditions for physical education and sports (PEaS) for all categories and groups of the population, including mass sports, increasing the level of provision of the population with sports facilities, and creating conditions for the preparation of the sports reserve [1]. As part of the national goal "Preservation of the Population, Health and Well-Being of People", the goal was set to increase the proportion of citizens systematically involved in the PEaS to 55 per cent by 2024 and to 70 per cent by 2030 [2]. The article presents an analysis of the most informative and reliable indicators characterising the development of sports and identifies trends in their development. The results of the study are relevant to the development and adjustment of regulatory documents, including the norms and requirements of the unified All-Russian Sports Classification (UARSC), the unified calendar plan for interregional, national and international sports events, and sports events (UCP), federal sports training standards (FSTS). Moreover, the results obtained are necessary for the further formation of the model of sports development, taking into account their differentiation into groups according to the specifics of competitive activities.